PEMAKNAAN KHALAYAK TERHADAP KONFLIK SELEBRITI PADA TAYANGAN INFOTAINMENT - Qudratullah Qudratullah (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
AbstractInfotainment news about artists that air on television is always unique and interesting to watch. This is caused by conflicts displayed on the television screen. To still be able to exist, celebrities carry out a strategy by creating a variety of controversial and behavioral behaviors which are then widely covered and broadcast by infotainment on television. The conflict news program carried out by these celebrities contained codes for each event. So this study tries to find out how the analysis of public receptions on the contents of messages in the reporting of celebrity conflicts in infotainment. This study uses a reception analysis method by conducting interviews with informants who have met certain criteria. The theory used is the Encoding-Decoding Theory by Stuart Hall. The results show that there are 3 reception categories in celebrity conflict news on the audience. Four people in the Dominant Hegemonic category, one in the Negotiated category, and one in the Oppositional category. Keywords: News, Celebrities, Infotainment, Reception Analysis, Encoding-Decoding.